Bimetallic Au@Pt@Au core–shell nanoparticles on graphene oxide nanosheets for high-performance H2O2 bi-directional sensing1. Issue 21 (7th June 2015) - Li, Xiao-Rong; Xu, Ming-Chen; Chen, Hong-Yuan; Xu, Jing-Juan
<x xml:space="preserve">Abstract</x> Synthesis of bimetallic Au@Pt@Au core–shell nanoparticles on graphene oxide (GO) nanosheets and their application for bi-directional determination of H2O2 from cancer cells.